OPTIMIZATION OF SWEET GUAVA (Psidium guajava, L) USING THE ACCEPTANCE TEST, RESPONSE SURFACE METHODOLOGY AND PREFERENCE MAP - MENEZES, CAMILA CARVALHO; BORGES, SORAIA VILELA; CARNEIRO, JOÃO DE DEUS SOUZA; CIRILLO, MARCELO ANGELO; PINHEIRO, ANA CARLA MARQUES; OLIVEIRA, LETÍCIA FERNANDES DE (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2012)
This study aimed to evaluate the influence of the independent variables concentration of citric acid, concentration of potassium sorbate, and pulp/sugar ratio on consumer acceptance for sweet guava. The results were analyzed using statistical methods such as preference map and response surface methodology to determine the influence of the independent variables. Response surface methodology alone proved insufficient to achieve an optimal formulation for the preparation of sweet guava. Based on preference mapping analysis, consumer preference was observed for treatments using higher concentrations of sugar and citric acid. Parameters of sweetness, appearance and texture influenced consumer preferences.